Pengobatan dan Edukasi Penyakit Skabies pada Anak Panti Asuhan Desa Pelintung, Medang Kampai Kota Dumai - Esy Maryanti; Enny Lestary; Ade Wirdayanto; Wira Firja; Muhammad Devlin (Universitas Serang Raya, 2023)
Abstract Scabies is a disease caused by a parasitic infestation; Sarcoptes scabiei var hominis. This disease is a neglected parasitic disease with symptoms of itching on the skin infested with Sarcoptes scabiei. This disease is not fatal but can interfere with daily activities in infected people. Scabies often occurs in people who live together in groups such as in dormitories and orphanages. The aim of this activity were to find out the incidence of scabies in orphanage children and to carry out treatment and provide education about scabies. This activity was carried out at the Pelintung Village orphanage, Medang Kampai District, Dumai City, Riau Province. A total of 53 children examined were found 28.3% positive for scabies and boys were more infested than girls. In children who were positive for scabies given topical therapy permethrin 5%. In addition to treatment, education was also provided about scabies and it was found that children’s knowledge before and after education had increased. It is hoped that this activity will continue to be carried out on an ongoing basis so that it can eradicate scabies in orphanages. Keywords : children, Sarcoptes scabiei, scabies, orphanage